Euthyroid and primarily hypothyroid patients develop milder and significantly more asymmetrical Graves ophthalmopathy. Issue 8 (15th February 2009) - Eckstein, A K; Lösch, C; Glowacka, D; Schott, M; Mann, K; Esser, J; Morgenthaler, N G
Abstract : Background and aims: Retrospective, observational study to compare clinical symptoms and TSH-receptor antibodies (TRAb) in Graves ophthalmopathy (GO) in euthyroid and primarily hypothyroid patients to those in hyperthyroid patients. Methods: Clinical symptoms (NOSPECS (severity) and CAS (activity) score), prevalence and levels of thyroid specific antibodies and the course of the disease were evaluated in 143 primarily hyperthyroid, 28 primarily euthyroid and 11 primarily hypothyroid patients with GO. Results: Patients with euthyroid/hypothyroid GO developed significantly less severe GO symptoms (NOSPECS score 4.4 vs 5.7; p = 0.03), less active GO (CAS score 3.9 vs 5.2; p = 0.002) and more asymmetrical disease (proptosis side difference: 1.9 mm vs 1.0 mm (p = 0.01); side difference of ⩾3 mm: 23% vs 4.8%) than hyperthyroid patients. TRAb levels 6 months after GO onset were significantly lower (2.2 IU/l, p = 0.02) in euthyroid/hypothyroid than in hyperthyroid patients (8.6 IU/l), as was the prevalence of both TRAb and thyroid peroxidase antibodies (75% vs 94.6%, p = 0.0008). Conclusions: The knowledge about the phenotype of GO in primarily euthyroid and hypothyroid patients is helpful for differential diagnosis and patient consultation. TRAb titres are very low in these patients, and the availability of a sensitive assay technique is therefore an important diagnostic tool in euthyroid and hypothyroid patients.